Availability of advance directives in the emergency department (Swiss Medical Weekly, 2020)
BACKGROUND Emergency departments (EDs) are crowded with critically ill patients, many of whom are no longer able to communicate with the emergency staff. Substitute decision makers are often unknown or not reachable in time. The availability of advance directives (ADs) among Swiss ED patients has not yet been evaluated. The purpose of this prospective survey was to investigate the prevalence of ADs among ED patients and to identify factors associated with the existence or absence of ADs. METHODS In a prospective survey, we enrolled consecutive patients from 10–30 July 2017 who visited a tertiary care ED. Patients completed a written, standardised and self-administrated questionnaire during the waiting time. The primary endpoint was the prevalence of ADs in ED patients. Secondarily, we defined predictors associated with the existence or absence of ADs. Two months after the first survey, there was a written follow-up survey asking patients without ADs whether they had completed an AD in the meantime. RESULTS Fifty-eight of 292 enrolled ED patients (19.9%) had a completed AD. Overall, 49.3% of the survey population was female. Patients having an AD were older (69.5 years, interquartile range [IQR] 57–81 vs 39 years, IQR 27–56) and had more comorbidities (67.2% vs 38.9%) compared with patients without ADs. The four leading reasons given for not having an AD were: 33.6% never considered completing one, 26% did not know about ADs, 14% preferred family to make decisions, 11.6% felt it was too early to make such a decision. Predictors for having an AD were older age (p